Community-based small ruminant breeding programs with livelihood benefits are becoming the nucleus for climate-resilient scaling in Ethiopia: Results from an ongoing community-based breeding program in Doyogena, Ethiopia - Habtegiorgis, Kebede; Haile, Aynalem; Getachew, Tesfaye; Ambaw, Gebermedihin; Recha, John W.M.; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In developed countries, national breeding programs have been implemented by well-organized breeder associations with full support from the state in a developed infrastructure and high-level capacity to run the breeding programs. Such breeding programs are successful in data recording and processing, and the evaluation of the best candidates for optimal breeding. However, adopting such breeding programs in developing countries was not successful due to a lack of support from government and poor infrastructure.